KONSUMSI MENURUT EKONOMI ISLAM DAN KAPITALIS - ALMIZAN ALMIZAN (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
Historically the economy of early Islam is far more developed than conventional economics. One of the important theory of Islamic and capitalism economics is related to consumption. In Islamic economics should consumed in order to find Ridha Allah SWT. A conviction and systems that can save the world from the greed of man as homo economicus. However, the rapid economic progress and the widespread network of conventional capitalism, consumption theory of Islam into the unknown in the academic world, especially in everyday life. However, the same progressiveness could bring the world in the unrecoverable and uncontrollable progressiveness. Progressive-power that inherent in the global capitalism has the tendency to lead the world into undetermined, injustice and hegemonic situation. This paper would discover this human’s live.